Augmented Reality-Assisted Assessment of Workplace Ergonomy - Yigitbas, Enes; Karch, Julian (Proceedings of the 18th International Conference on PErvasive Technologies Related to Assistive Environments (PETRA 2025))

Blackbox Unit Testing of Virtual Reality Applications - Geil, Manuel; Wübbeke, Andreas; Yigitbas, Enes (Proceedings of the 27th International Conference on Human-Computer Interaction (HCII 2025))

Monitoring phage infection and lysis of surface-immobilized bacteria by QCM-D - Pothineni, Bhanu K.; Probst, René; Kiefer, Dorothee; Dobretzberger, Verena; Barišić, Ivan; Grundmeier, Guido; Keller, Adrian (Analytical and Bioanalytical Chemistry)
Abstract While being a promising approach for the treatment of infections caused by drug-resistant, pathogenic bacteria, the clinical implementation of phage therapy still faces several challenges. One of these challenges lies in the high strain-specificity of most bacteriophages, which makes it necessary to screen large phage collections against the target pathogens in order to identify suitable candidates for the formulations of personalized therapeutic phage cocktails. In this work, we evaluate the potential of quartz crystal microbalance with dissipation monitoring (QCM-D) to identify and detect phage infection and subsequent lysis of bacteria immobilized on the surfaces of the QCM-D sensors. Using lytic Escherichia coli phage T7 as a model, we show that phage infection of E. coli cells results in various unique alterations in the behaviors of the frequency (Δ f ) and dissipation (Δ D ) signals, which are not observed during exposure of the E. coli strain to non-infectious Bacillus subtilis phage phi29 at similar concentration. To aid future phage screening campaigns, we furthermore identify a single measurement parameter, i.e., the spread between the different overtones of Δ D , that can be used to detect phage-induced lysis. For T7 infection of E. coli , this is achieved within 4 h after inoculation, including immobilization and growth of the bacteria on the sensor surface, as well as the completed phage propagation cycle. Given the commercial availability of highly automated multichannel systems and the fact that this approach does not require any sensor modifications, QCM-D has the potential to become a valuable tool for screening medium-sized phage collections against target pathogens. Graphical Abstract

Counting two-step nilpotent wildly ramified extensions of function fields - Gundlach, Fabian; Seguin, Beranger Fabrice (arXiv:2502.18207)
We study the asymptotic distribution of wildly ramified extensions of function fields in characteristic $p > 2$, focusing on (certain) $p$-groups of nilpotency class at most $2$. Rather than the discriminant, we count extensions according to an invariant describing the last jump in the ramification filtration at each place. We prove a local-global principle relating the distribution of extensions over global function fields to their distribution over local fields, leading to an asymptotic formula for the number of extensions with a given global last-jump invariant. A key ingredient is Abrashkin's nilpotent Artin-Schreier theory, which lets us parametrize extensions and obtain bounds on the ramification of local extensions by estimating the number of solutions to certain polynomial equations over finite fields.

Zusammenhänge zwischen dem Rollenverständnis angehender Lehrpersonen und ihren Einstellungen zu Mehrsprachigkeit - Meier, Jana; Meusel, Sarah

Prediction of the Frictional Power Distribution in the Tire Contact Patch Based on an Empirical Tire Model and an Artificial Neural Network - Muth, Lars; Zharia, Raphael; Sahin, Hürkan; Sextro, Walter (Tire Science and Technology)
To predict and prevent uneven tire wear in addition to a reduction of overall tire wear, it is essential to estimate not only the total amount of wear but also how the wear is distributed across the tire width. This requires knowledge of the frictional power distribution in the tire contact patch, which is the basis for calculating tire wear using a wear law. Usually, only 3D structural tire models can generate such distributed contact results. However, they involve high computational costs and cannot be used for comprehensive optimization of a vehicle’s suspension system with respect to tire wear characteristics. Hence, this contribution presents a methodology on how to accelerate the prediction of the frictional power distribution using two components: The structural tire model is replaced by an empirical tire model that on its own is not able to generate distributed contact results. Therefore, an artificial neural network is trained to predict the desired contact results from the kinematic quantities calculated by the empirical tire model. In the initial training phase, both components are fitted to data generated by the original complex tire model. After training, the empirical tire model can replace the structural tire model in vehicle simulations, resulting in significantly shorter calculation times. The simulation results are fed into the artificial neural network, which predicts the frictional power distributions over the tire width with negligible additional effort. Overall, the methodology reduces calculation time for the prediction of tire wear based on virtual test drives to approximately 25% of the time needed when using structural tire models.

Towards reliable HETP values: Lessons learned from standardized separation efficiency measurements - Neumann, Maximilian; Xia, Marc; Pöschmann, René; Merkel, Amelie; Staud, Rolf; Schneider, Hannes; Ehlert, Thomas; Paschold, Jürgen; Müller, Steffen; Harding, Laura-Selin; Neukäufer, Johannes; Hiller, Christoph; et al. (Separation and Purification Technology)

Locally homogeneous Axiom A flows II: geometric structures for Anosov subgroups - Delarue, Benjamin; Monclair, Daniel; Sanders, Andrew (arXiv:2502.20195)
Given a non-compact semisimple real Lie group $G$ and an Anosov subgroup $Γ$, we utilize the correspondence between $\mathbb R$-valued additive characters on Levi subgroups $L$ of $G$ and $\mathbb R$-affine homogeneous line bundles over $G/L$ to systematically construct families of non-empty domains of proper discontinuity for the $Γ$-action. If $Γ$ is torsion-free, the analytic dynamical systems on the quotients are Axiom A, and assemble into a single partially hyperbolic multiflow. Each Axiom A system admits global analytic stable/unstable foliations with non-wandering set a single basic set on which the flow is conjugate to Sambarino's refraction flow, establishing that all refraction flows arise in this fashion. Furthermore, the $\mathbb R$-valued additive character is regular if and only if the associated Axiom A system admits a compatible pseudo-Riemannian metric and contact structure, which we relate to the Poisson structure on the dual of the Lie algebra of $G$.

Competency Profiles of PCK Using Unsupervised Learning: What Implications for the Structures of pPCK Emerge From Non-Hierarchical Analyses? - Zeller, Jannis; Riese, Josef (Journal of Research in Science Teaching)
There have been several attempts to conceptualize and operationalize pedagogical content knowledge (PCK) in the context of teachers' professional competencies. A recent and popular model is the Refined Consensus Model (RCM), which proposes a framework of dispositional competencies (personal PCK—pPCK) that influence more action-related competencies (enacted PCK—ePCK) and vice versa. However, descriptions of the internal structure of pPCK and possible knowledge domains that might develop independently are still limited, being either primarily theoretically motivated or strictly hierarchical and therefore of limited use, for example, for formative feedback and further development of the RCM. Meanwhile, a non-hierarchical differentiation for the ePCK regarding the plan-teach-reflect cycle has emerged. In this study, we present an exploratory computational approach to investigate pre-service teachers' pPCK for a similar non-hierarchical structure using a large dataset of responses to a pPCK questionnaire (N=846). We drew on theoretical foundations and previous empirical findings to achieve interpretability by integrating this external knowledge into our analyses using the Computational Grounded Theory (CGT) framework. The results of a cluster analysis of the pPCK scores indicate the emergence of prototypical groups, which we refer to as competency profiles: (1) a group with low performance, (2) a group with relatively advanced competency in using pPCK to create instructional elements, (3) a group with relatively advanced competency in using pPCK to assess and analyze described instructional elements, and (4) a group with high performance. These groups show tendencies for certain language usage, which we analyze using a structural topic model in a CGT-inspired pattern refinement step. We verify these patterns by demonstrating the ability of a machine learning model to predict the competency profile assignments. Finally, we discuss some implications of the results for the further development of the RCM and their potential usability for an automated formative assessment.
Keywords: computational grounded theory; language analysis; machine learning; pedagogical content knowledge; unsupervised learning

Metatextuelle Textprozeduren: Gliedern und Zusammenfassendes Wiedergeben. - Rezat, Sara; Feilke, Helmuth (Zusammen:gedacht. Transdisziplinäe Perspektiven auf Literalität und Schreiben im Kontext von Mehrsprachigkeit. Festschrift für Sabine Schmölzer-Eibinger.)

Physik lernen durch Erklären? - Evaluation eines Seminarkonzepts für Sachunterrichtsstudierende - Hörnlein, Madeleine (die hochschullehre)

Wassermanagement und Wasserlandschaften frühneuzeitlicher Montanregionen: Erzgebirge – Harz – Potosí - Silvestri, Marco (Landschaft: Kultur-, Natur-, Wirtschafts- und Erfahrungsräume)

How curriculum materials can contribute to implementing instructional innovations: the case of enactment of strategy instruction - Dröse, Jennifer; Ahlemeyer, Leonie; Prediger, Susanne (ZDM – Mathematics Education)

Concept Maps zur Reflexion für einen professionellen Umgang mit Vielfalt im Mathematikunterricht - Dröse, Jennifer; Bruns, Julia; Häsel-Weide, Uta (die hochschullehre)

Interkulturelle Kompetenzen in der Musikwissenschaft. Potenziale hybrider Kooperationsseminare - Adler, Luise (Paderborner Beiträge 2024. die hochschullehre - Themenheft 2025)
Auslandsaufenthalte von Studierenden sind im Fach Musikwissenschaft an der Universität Paderborn eher eine Ausnahme. Das hat unterschiedliche Gründe, unter anderem die nicht vorhandene curriculare Verankerung. Dabei belegen diverse Untersuchungen, dass solche Aufenthalte den interkulturellen Kompetenzerwerb und damit Fähigkeiten fördern, die unabhängig vom Fach in einer globalisierten Welt immer größere Relevanz im Berufsleben einnehmen. Im Projekt wurde ein hybrides internationales Kooperationsseminar entwickelt und durchgeführt sowie in Bezug auf den Erwerb dieser wichtigen Schlüsselqualifikation evaluiert. Die Auswertung der unter anderem durch Fragebögen erhobenen Entwicklung konnte deutlich die positiven Auswirkungen eines hybriden Kooperationsseminars auf interkulturelle Kompetenzen, die Auseinandersetzung mit verschiedensten Aspekten einer anderen Kultur, darunter Geschichte, Politik, (Post-)Kolonialismus und den eigenen Privilegien aufzeigen. Zudem lassen sich aus der Evaluation weitere Ideen für rein digitale Formate ableiten.
Keywords: interkulturelle Kompetenz; interkulturelle Sensitivität; Musikwissenschaft; digitale Lehre; hybride Lehre; intercultural competence; intercultural sensitivity; musicology; digital education; hybrid education

Influence de l'utilisation de la réalité augmentée lors des expériences chimiques sur la connexion des niveaux de représentation dans les explications des élèves - Peeters, Hendrik; Habig, Sebastian; Fechner, Sabine (Actes des XIIIe Rencontres scientifiques de l’ARDIST)

Dynamic modulations of effective brain connectivity associated with postural instability during multi-joint compound movement on compliant surface - Lehmann, Tim; Visser, Anton Samuel; Havers, Tim; Büchel, Daniel; Baumeister, Jochen (Experimental Brain Research)
Abstract Random fluctuations in somatosensory signals affect the ability of effectively coordinating multimodal information pertaining to the postural state during movement. Therefore, this study aimed to investigate the impact of a compliant surface on cortico-cortical causal information flow during multi-joint compound movements. Fifteen healthy adults (7 female / 8 male, 25.9 ± 4.0 years) performed 5 × 20 repetitions of bodyweight squats on firm and compliant surface. Motor behavior was quantified by center of pressure (CoP) displacements, hip movement and the root mean square of the rectus femoris activity. Using source space analysis, renormalized partial directed coherence (rPDC) computed subject-level multivariate effective brain connectivity of sensorimotor nodes. Bootstrap statistics revealed significantly decreased medio-lateral CoP displacement ( p < 0.001), significantly increased velocity of medio-lateral hip motion ( p < 0.001) as well as significantly lower rectus femoris activity ( p < 0.01) in the compliant surface condition. On the cortical level, rPDC showed significantly modulated information flow in theta and beta frequencies for fronto-parietal edges ( p < 0.01) only during the concentric phase of the movement. The compliant surface led to increased difficulties controlling hip but not center of pressure motion in the medio-lateral plane. Moreover, a decreased activation of the prime movers accompanied by modulations of effective brain connectivity among fronto-central nodes may point to altered demands on sensorimotor information processing in presence of sensory noise when performing bodyweight squats on compliant surface. Further studies are needed to evaluate a potential benefit for athletic and clinical populations.

Paradigmenwechsel und Metapher. Ein Weg zur Gesellschaft der Nachhaltigkeit? - Albus, Vanessa (Nachhaltigkeit in der Medienkommunikation. Ethische Anforderungen und praktische Lösungsansätze)

Gendersensibler Philosophie- und Ethikunterricht. Standortbestimmung, Desiderate und Diskussionen - Albus, Vanessa (Selbstverständnisse der Philosophiedidaktik zwischen Fachphilosophie und Interdisziplinarität)

Evaluation eines Lehrmoduls zur Stärkung der Demokratiebildungskompetenz von Lehramtsstudierenden - Wehde, Janis (die hochschullehre)
In diesem Beitrag wird ein zwei Sitzungen umfassendes, flexibel integrierbares Lehrmodul zur Stärkung der Demokratiebildungskompetenz von Lehramtsstudierenden evaluiert. Dazu werden 101 schriftliche Reflexionen von Studierenden aus drei bildungswissenschaftlichen Hochschulseminaren aus dem Wintersemester 2022/2023 und dem Sommersemester 2023 anhand der Text-Sortier-Technik ausgewertet. Die Evaluationsergebnisse verdeutlichen die studentischen Lernaktivitäten in den Kompetenzbereichen Werte, Einstellungen und Fähigkeiten für eine demokratische Kultur. Zudem wurden die Kenntnisse der Studierenden zur methodischen Gestaltung von demokratischen Aushandlungsprozessen im Unterrichts- und Schulkontext erweitert. Demnach konnte die Wirksamkeit des Lernmoduls auf der Prozess- und Ergebnisdimension hochschulischen Lernens plausibilisiert werden.